A study of the influence of cooling water on the structural modes and vibro-acoustic characteristics of a gasoline engine. (March 2016) - Liu, Rui-jun; Hao, Zhi-yong; Xu, Wang; Zheng, Xu; Mao, Jie; Xiong, Fei; Yang, Wen-ying
Highlights: The influence of the cooling water on the vibration mode and damping characteristics. A systematic evaluation approach taking the fluid influence into account. The cooling water will increase fluid related modes, but not change the other modes. The cooling water will change the damping and vibro-acoustic characteristics. The cooling water effect has doubled the mass but not stiffness matrix scale factor. Abstract: The influence of the cooling water on the vibration mode and damping characteristics of an engine was evaluated through experimental and simulation methods. The wet mode method of the fluid–structure interaction field was applied in numerical analysis, which led to several significant conclusions. Several additional fluid related modes were present when the effect of cooling water was considered. Meanwhile, the frequencies of other modes were almost the same. On the other hand, the damping characteristics of an engine were changed while the cooling water was used. For Rayleigh damping, the cooling water effect has made the mass matrix scale factor α nearly double and the stiffness matrix scale factor β almost unchanged. The engine surface vibration acceleration magnitude was calculated by means of the multi-body dynamic analysis. It was shown that the calculated vibration acceleration magnitude was close to the measured one when the cooling water was taken into account. Furthermore, acoustic simulation results were estimated by Boundary Element Method, which revealed that the sound power level of the radiation noise of most engine components was lower than that with the fluid structure interaction model being applied in the engine block modeling. The overall sound power level of the whole engine radiation noise was increased by 3.6 dB when the effect of the cooling water was considered, which demonstrated that the effect of the cooling water on the engine vibro-acoustic characteristics should not be neglected during the computation. This paper has disclosed the influences of the cooling water on the engine structural modes, damping, sound power level of the engine radiation noise and a systematic approach for evaluation of the influences.